Association of actin-myosin interaction biomarkers and fibrosis with myocardial inflammatory changes in patients with idiopathic atrial fibrillation. (25th November 2020) - Gusakova, A; Batalov, R; Shelemehov, A; Rogovskaya, Y; Suslova, T
Abstract: Introduction: Myocarditis and inflammatory changes in the myocardium are causes of the development and progression of atrial fibrillation (AF). Inflammatory processes may also lead to the development of fibrosis, electrical and structural myocardial remodeling, adversely affecting the effectiveness of interventional treatment. Purpose: To assess the dynamics and to identify relationships between serum levels of tropomyosin I, myosin light chain kinase (MLCK), myosin heavy (MYH7) and light chains (CMLC), transforming growth factor (TGF-β1) and myocardial inflammatory changes in patients with idiopathic AF. Methods: Subjects were 40 patients (41.0±9.2 y.o.) with idiopathic AF (arrhythmic history constituted 4.9±3.9 years). Paroxysmal AF (ParAF) was detected in 37% (n=15), persistent AF (PerAF)–30% (n=12), and long-standing persistent (LPerAF)–33% (n=13). All patients underwent radiofrequency ablation (RFA) of the pulmonary veins and endomyocardial byopsy with histologic and immunohistochemical studies. Depending on the results of histological study, the patients were divided into 2 groups: 1–with active lymphocytic myocarditis (ALM) (n=22); 2–with lymphocytic infiltration (IL) (n=18). Blood for biomarkers evaluation was collected prior to RFA and in 6 months after RFA. Results: In patients with ALM levels of biomarkers significant differed depending on the form of AF. In patients with PerAF, the levels of MYH7, MLCK and tropomyosin I were significantly lower than in patients with ParAF (p<0.005). In 6 months the levels of MLCK, tropomyosin I, and CMLC significantly differed in patients with ALM depending on the form of AF (p<0.05). In patients with PerAF in the group 1, the concentrations of MYH7, CMLC, and tropomyosin I were lower, than the group 2 (p<0.05). In 6 months in patients with PerAF, the TGF-β1 levels also differed between groups 1 and 2 (Me: 24.09 and 40.34 ng/ml, p<0.05). The content of TGF-β1 before the RFA and in 6 months in patients with PerAF was associated with the development of infiltration in 6 months after RFA (R=0.696, p=0.025). In LPerAF patients we showed correlation between the content of TGF-β1 and the severity of fibrosis in 6 months after RFA (R=0.607, p=0.047). At LPerAF TGF-β1 content correlated with degree of fibrosis in 6 months after RFA (R=0.607, p=0.047). The relationship between the form of AF and the inflammatory changes were identified (r=0.32, p=0.049). Thus, in patients with LPerAF and PerAF, ALM was diagnosed in 69% and 50% of cases, while in patients with ParAF the frequency of ALM detection constituted 33%. Conclusion: Our study showed that ALM was detected in 55% of patients, and IL–in 45% of cases. Significant differences in the levels of MYH7, MLCK, CLCK, tropomyosin I in patients with PerAF and various forms of inflammatory myocardial changes were revealed. The content of the TGF-β1 is reduced in ALM in patients with PerAFP. The incidence of ALM was higher in patients with long-term persistent AF. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Cardiology Research Institute, Tomsk NRMC